Pemberdayaan Masyarakat dalam Rehabilitasi Hutan melalui Penerapan Teknologi Geospasial di Desa Jeruk Manis, Lombok Timur - Azis, Abdul; Islam, Rudi (Journal of Community Development and Empowerment, 2025)
Forest rehabilitation is a strategic effort to maintain ecosystem sustainability and mitigate climate change. Jeruk Manis Village, located in Sikur Subdistrict, East Lombok Regency, is one of the areas with forest zones that have suffered significant degradation due to human activities and environmental pressures. This community service initiative aims to empower local communities in forest rehabilitation efforts through the application of geospatial technology as a tool for planning and monitoring. The activities were carried out using a participatory approach, including training in participatory mapping using Geographic Information System (GIS) applications, identification of critical lands, and replanting of degraded forest areas. The results of the activities showed increased community capacity in understanding the use of geospatial technology for forest area mapping, as well as greater collective awareness of the importance of forest conservation. In addition, the community was able to produce basic spatial maps that can serve as references for sustainable rehabilitation programs. The application of geospatial technology has proven effective in strengthening community involvement and enhancing efficiency in the rehabilitation process. It is hoped that this initiative can serve as a model for community empowerment that can be replicated in other areas with similar conditions. Collaboration between the community, village government, and the service team is the key to achieving inclusive and data-driven forest rehabilitation.